1998
DOI: 10.1021/la980102r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Polyaniline-Coated Polystyrene Latexes

Abstract: The surface compositions of seven polyaniline (PAni)-coated polystyrene (PS) latexes have been investigated by X-ray photoelectron spectroscopy. This technique was used to assess the uniformity of the PAni overlayers deposited onto micrometer-sized, poly(N-vinylpyrrolidone) (PNVP)-stabilized PS latex particles under various synthesis conditions. Peak fitting of the N(1s) core-line spectra provided evidence for the presence of both PAni and the PNVP stabilizer at the surface of the PS latex. Nonuniform PAni coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 19 publications
(49 reference statements)
5
84
3
Order By: Relevance
“…[20] These results were supported by SEM studies, which showed that PPY overlayers appeared far smoother than PANI overlayers.…”
Section: Probing the Surface Of The Coated Latex Particlesmentioning
confidence: 71%
“…[20] These results were supported by SEM studies, which showed that PPY overlayers appeared far smoother than PANI overlayers.…”
Section: Probing the Surface Of The Coated Latex Particlesmentioning
confidence: 71%
“…For composites containing conducting particles with a high aspect ratio, the percolation limit drops below 5 vol % of the conducting component. 21,22 The nonconducting particles coated with conducting polymers also have a lower percolation limit [23][24][25] compared with composites in which compact conducting particles are dispersed in the non-conducting matrix, where the formation of conducting pathways is much more difficult. In the case of coated sawdust, both of these effects are combined, and the observation of a percolation threshold below 5 wt % of conducting polymer is thus not surprising.…”
Section: Conductivity and Its Thermal Stabilitymentioning
confidence: 99%
“…16 In order to increase the processability and mechanical properties of PAni, significant efforts have been done in preparation of blends based on PAni with other appropriate polymers that have good physical properties, 17,18 such as polystyrene, 19 polyamide, 20 and polysaccharides like cellulose, starch and chitosan. [21][22][23] Recently, in addition of the mixture of PAni with other polymers, it has been sought to improve such properties through the preparation of hybrid organic/inorganic composites by the incorporation of metal oxides (such as WO 3 28 or mesoporous materials such as SBA-15 and MCM-41, 29,30 since they combine the advantages of conjugated conducting polymers and these fillers offering special properties arising from the combination of each component.…”
Section: Introductionmentioning
confidence: 99%